Maize root growth angles become steeper under low N conditions - Trachsel, S.; Kaeppler, S.M.; Brown, K.M.; Lynch, J.P. (Field crops research, 2013)
Root traits that increase the speed and effectiveness of subsoil foraging may enhance nitrogen acquisition in leaching environments. We investigated root depth distribution of maize genotypes across the cropping cycle, effects of root angles on plant performance and potential plastic responses of root growth angles to nitrogen fertilization. We focus on genetic variation for growth angles of crown and brace roots among 108 inbred lines of maize in high and low nitrogen field environments in the USA and South Africa. Root angles of crown roots were significantly associated with rooting depth calculated as the depth containing 95% of the root mass (D95). The number of brace roots as well as rooting depth (D95) increased between 43 days after planting (DAP) and flowering, but did not show any major changes between flowering and physiological maturity. Brace root branching increased between 43 DAP and flowering and showed reductions between flowering and physiological maturity. Under well-fertilized conditions genotypes initially selected as ‘steep’ and ‘shallow’ did not alter their root angles. Brace and crown root angles became up to 18° steeper under nitrogen deficient conditions. Increases in root angles under nitrogen deficient conditions were more accentuated for shallow genotypes, resulting in root angles and rooting depths similar to the ones measured for steep genotypes. Steeper root angles enabled plastic genotypes to potentially explore similar soil volumes under nitrogen deficient conditions as steep genotypes, thereby not incurring any reductions in grain yield compared to genotypes constitutively forming steep root angles. Additive main and multiplicative interaction effects (AMMI) analysis revealed that out of 29 genotypes best adapted to 4 different nitrogen fertilizer treatment-by-location combinations, 11 were steep, 11 were plastic and 7 were shallow genotypes. The number of plastic genotypes among the adapted entries was disproportionately high compared to 6 that could be anticipated based on the distribution in the entire genotypic set. We postulate that modulation of rooting depth by root growth angles is important for nitrogen acquisition by positioning roots in soil domains with the greatest nitrogen availability. Genotypic variation in root growth angles and the plasticity of root growth angles in response to nitrogen may be useful in breeding crops with improved nitrogen acquisition.